Glyphosate behavior in a Rhodic Oxisol under no-till and conventional agricultural systems - Prata,Fábio (2005)
The behavior of glyphosate in a Rhodic Oxisol, collected from fields under no-till and conventional management systems in Ponta Grossa, Parana state (Brazil) was investigated. Both agricultural systems had been in production for 23 years. Glyphosate mineralization, soil-bound forms, sorption and desorption kinetics, sorption/desorption batch experiments, and soil glyphosate phythoavailability (to Panicum maximum) were determined. The mineralization experiment was set up in a completely randomized design with a 2 x 2 factorial scheme (two management systems and two 14C radiolabelled positions in the glyphosate), with five replicates. 14CO2 evolution was measured in 7-day intervals during 63 days. The glyphosate sorption kinetics was investigated in a batch experiment, employing a glyphosate concentration of 0.84 mg L-1. The equilibration solution was 0.01 mol L-1 CaCl2 and the equilibration times were 0, 10, 30, 60, 120, 240, and 360 min. Sorption/desorption of glyphosate was also investigated using equilibrium batch experiments. Five different concentrations of the herbicide were used for sorption (0.42, 0.84, 1.68, 3.36, and 6.72 mg L-1) and one concentration for desorption. Glyphosate phytoavailability was analyzed in a 2 x 5 factorial scheme with two management systems and five glyphosate concentrations added to soil (0, 4.2, 8.4, 42.0, and 210.0 µg g-1) in a completely randomized design. Phytotoxicity symptoms in P. maximum were evaluated for different periods. The soil under both management systems showed high glyphosate sorption, which impeded its desorption and impaired the mineralization in the soil solution. Practically the total amount of the applied glyphosate was quickly sorbed (over 90 % sorbed within 10 min). Glyphosate bound to residues did not have adverse effects on P. maximum growth. The mineralization of glyphosate was faster under no-till and aminomethylphosphonic acid was the main glyphosate metabolite.